Assessment of vitamin D and its association with cardiovascular disease risk factors in an adult migrant population: An audit of patient records at a Community Health Centre in Kensington, Melbourne, Australia - Ruwanpathirana, T.; Reid, Christopher; Owen, A.; Fong, D.; Gowda, U.; Renzaho, A. (BioMed Central Ltd., 2014)
Background: Vitamin D deficiency is a global public health problem associated with increased risk of cardio-metabolic diseases and osteoarthritis. Migrants with dark skin settled in temperate climates are at greater risk of both vitamin D deficiency and cardiovascular diseases. This study aims to identify the risk of vitamin D deficiency and associations with cardiovascular disease in a migrant population in Australia. Methods: An audit was carried out at a Community Health Service in Kensington, Melbourne which, services a large migrant population. Data from the clinical records of all adults who visited the medical centre at least once during the period from 1st January 2010 to 31st December 2012 was extracted. The future (10 year) coronary heart disease risk was estimated using Framingham Risk Score. Results: The centre has given higher priority to vitamin D testing in migrants, those middle-aged, females and those with diabetes and osteoarthritis. Migrants from countries located in lower latitude regions (Latitude N230 to S230) were 1.48 (95% C.I. 1.32-1.65) times more likely to develop vitamin D deficiency post migration and 0.44 (95% C.I. 0.31-0.62) times less likely to have a >15% 10-year risk of coronary heart disease when compared to their Australian-born counterparts. Conclusions: Adherence to a high risk strategy for vitamin D testing was observed in the centre. Pre-migration latitude is an important factor for vitamin D deficiency (lower the latitude higher the risk) and in predicting future risk of cardiovascular disease in migrants. These findings suggest that a targeted approach for vitamin D testing, including zone of origin might better identify individuals at higher risk of both vitamin D deficiency and cardiovascular disease.